Surface Wetting Characterization, Contact Angle, and Fundamentals - Law, Kock-Yee.; Zhao, Hong.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book describes key basic concepts in surface and clarifies fundamental issues that lead to misconceptions in wetting and contact angle interpretation. A set of contact angle measurement protocols is summarized and may be served as guidelines for future standardization in this field. The authors also discuss issues related to surface definitions and terminologies.
1.Background -- 2.Contact Angle Measurements and Surface Characterization Techniques -- 3.Wetting on Flat and Smooth Surfaces -- 4.Wetting on Rough Surfaces -- 5.What Do Contact Angles Measure? -- 6.Terminologies and Definitions -- 7 Determination of Solid Surface Tension by Contact Angle -- 8 Summary and Final Remarks.
Keywords: Surfaces (Technology).; Thin films; Fluid mechanics; Continuum mechanics; Surfaces (Physics).; Surfaces, Interfaces and Thin Film; Engineering Fluid Dynamics; Continuum Mechanics; Surface and Interface and Thin Film